Everyday ethics: moral theology and the practices of ordinary life - Lamb, Michael; Williams, Brian A. (Georgetown University Press, 2019)
Introduction : contextualizing everyday ethics: moral theology meets anthropology and the social sciences / Michael Lamb and Brian A. Williams -- Evaluating Banner's proposal : interdisciplinary perspectives on meaning and method -- Toward an ethics of social practice / Molly Farneth -- Engaging the everyday in womanist ethics and Mujerista theology / Stephanie Mota Thurston -- Social anthropology, ethnography, and the ordinary / Morgan Clarke -- "The everyday" against the "and" in "theology and social science" / Brian Brock -- Practices of everyday ethics : extending the proposal -- Forming humanity : practices of education Christianly considered / Jennifer Herdt -- Social anthropology, neighbor-love, and the ethics of humanitarianism / Eric Gregory -- The elimination of the human within the technological society / Craig M. Gay -- On new new things : work and Christian thought in flexible capitalism / Philip Lorish -- The everyday ethics of borrowing and spending : evaluating economic risk and reward / Justin Welby -- Sharing tables : the embodied ethics of eating and joining / Rachel Muers -- Everyday ethics : a future for moral theology? -- The tasks of Christian ethics : theology, ethnography, and the conundrums of the cultural turn / Luke Bretherton -- Sacramental ethics and the future of moral theology / Charles Mathewes -- Confessions of a moderately (un)repentant sinner / Michael Banner -- Appendix. Everyday ethics : a bibliographic essay / Patrick McKearney -- Notes on contributors.